Everything but the Kitchen Sink: From Netnography to Progressive Web Application (PWA) Heuristics for Design and Development of the Sarawak Digital Cultural Heritage Information System - Nurfarahani, Norman Anuar (Universiti Malaysia Sarawak, 2023)
Digitization enables us to fend against the vulnerability and fragility of intangible and tangible knowledge or material culture, allowing long-term storage of information storage and accessibility. The need to conduct digital crowdsourcing stems from knowing that current ethnographic research is inefficient for completing the documentation process because it is time and cost-consuming has a language barrier and lacks expertise from each ethnicity. Despite different cultural agencies and government bodies overseeing the cultural efforts in Sarawak, there has not yet been a well-established information system to document and present the material culture for public access. The need to develop a new usability checklist for Progressive Web Application (PWA) stems from knowing that the available heuristics, which are catered for general usability purposes are not comprehensive enough to evaluate PWA due to its unique features. Recognising these problems, therefore the aim of this research was three-fold: (1) To utilize social media crowdsourcing in documenting Sarawak's cultural heritage; (2) To design and develop a one-stop information system for Sarawak’s cultural heritage; and (3) To develop a domain-specific heuristic for Progressive Web Application (PWA). A mix of methods was implemented for each of the different research stages. The first stage of the research utilizing Netnography via social media has resulted in 342 validated cultural heritage information with 88.4% reliability and validity. Artefacts and costumes cover the highest percentages of the data collected, 36.5% and 34.2%, respectively. Regarding the efficacy of social media platforms used to collect data, it was found that WhatsApp and Facebook were the most effective, with 46.2% and 43% of the information obtained through these mediums. The second stage of the research presented the outcome of the Sarawak Digital Cultural Heritage Information System (CULTAGE) PWA design and development. The process began by conducting Focus Group sessions to understand user requirements, coming up with proposed design ideas, and developing the web application, and ended with a user experience evaluation using the User Experience Questionnaire (UEQ). Overall, the CULTAGE-PWA received an average impression due to the evaluation procedure. Further Importance Performance Analysis (IPA) indicated the attributes associated with the CULTAGE-PWA fell under the “Possible Overkill”, meaning adequately developed and “Low Priority” in terms of importance and product requirement. The final stage of the research has developed 15 usability heuristics principles for PWA (PWAUH) using the heuristics development methodology by Rusu et al. (2011). This usability checklist was thoroughly validated and refined according to the systematic development method and through an expert validation survey and Heuristic Evaluation on 3 PWA sites.